(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Cross-contamination in oral surgery settings poses significant risks to both patients and healthcare providers. Dental surgery assistants (DSAs) play a crucial role in maintaining infection control protocols to prevent the transmission of pathogens. This paper explores the responsibilities of DSAs in sterilization, instrument handling, personal protective equipment (PPE) usage, and environmental disinfection. Additionally, we present data on compliance rates and best practices to minimize cross-contamination risks.